Update on primary cutaneous T-cell lymphomas rare subtypes (Dermatology Reports, 2024)
Rare subtypes of cutaneous T-cell lymphomas (CTCL) include four entities, primary cutaneous γδ T-cell lymphoma, primary cutaneous CD8+ aggressive epidermotropic cytotoxic T-cell lymphoma, and primary cutaneous CD4+ small/medium T-cell lymphoproliferative disorders, primary cutaneous acral CD8+ T-cell lymphoma, which were previously considered provisional and are now included in the new 5th World Health Organization classification of hematolymphoid tumors as distinct entities. An updated summary of the clinical, histological, and genomic characteristics of these uncommon CTCL subtypes is given in this review, with a focus on the growing body of knowledge regarding their classification and possible treatment strategies.